A Critical Discourse Analysis of NBC News Entitles' Anti-Asian Hate Incident Reports Nearly Doubled in March, New Data Says' - Annisa Indah Sukma; Zakie Asidiky (Journal of English Language Studies, 2022)
This research aimed to critically discover the author's ideology in the text entitled "Anti-Asian hate incident reports nearly doubled in March, new data says." In the analysis, the researchers used a qualitative method along with Fairclough's CDA model. As a result, it implied that Americans looked down on Asian-Americans, Americans took their stress out due to Covid-19 on Asian-Americans, Asian woman were the biggest victim in Asian hate, some Asian-Americans living in the U.S. had low economic levels, and the media had a big role in the development of Asian hate cases.  This research result can help more people understand and reduce racism, at least by understanding that human status is the same regardless of race, gender, economy, or religion.